SISTEM PENDUKUNG KEPUTUSAN SELEKSI KELAYAKAN PROPOSAL PENELITIAN DOSEN MENGGUNAKAN METODE TOPSIS DAN SAW - Ariyana, Renna Yanwsatika (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2018)
Research proposal selection process involving lecturers at the Institute for Research and Community Service (LPPM) must be carried out proportionally and professionally in accordance with established criteria and standards for management, assessment and funding. However, there are problems faced by LPPM, namely the lack of reviewers, differences in assessment styles, the number of diverse scientific studies, and the element of subjectivity are some of the challenge factors when selecting research proposals. There needs to be a decision support system that can be used as an alternative decision making in conducting research proposal selection. In this study we used a combination of Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) and Simple Additive Weighting (SAW) methods using five assessment criteria, namely: the ability of presentation and mastery of the material, the problem under study, research method, research output, and feasibility resource. Based on the results of the study, the results of the same calculation obtained by combining the TOPSIS method and SAW using 20 data samples with the value of accuracy between manual calculation and the system reaching 100%.